(untitled) (Cadernos de Sociomuseologia, 2021)
The project for Registration of off-road practices as intangible heritage and implementation of the Off-Road Ecomuseum in Nova Lima is a popular initiative that seeks to safeguard tradition and the benefits generated by off-road practices on the city’s trails. This is a pioneer initiative in the country and has a multidisciplinary character, as it involves three major areas: sport, culture and tourism. From the first indigenous occupations in Minas Gerais, through pioneers, pathfinders, drovers, rural producers who transported their items for sale and to local markets to the present day, the trails of Nova Lima are traveled by sportsmen and tourists. Thus, the aim is to use the trails from their conception as places of memory Keywords: Ecomuseum, culture, tourism, ecotourism, territory.